(untitled) (Mūzikas akadēmijas raksti, 2024)
It is typical of the language of the new music that the characteristic features of an individual work cannot be discussed in depth without the prior establishment of a relatively original set of analytical tools. Helena Tulve’s Vertige for amplified piano is no exception. Although the style of the work can be related to the different streams of art music at the end of the 20th century, e.g. the spectral music, the unfolding of the musical canvas of the composition cannot be explained exclusively in terms of French spectralism. In this paper I try to establish a set of analytical tools which help to describe the structural features of the aforementioned work. In particular, I will concentrate on the voice leading and its relations to the other aspects of the tonal structure of the work.